Influence of Estrogen on the NSCLC Microenvironment: A Comprehensive Picture and Clinical Implications - Smida, Tanner; Bruno, Tullia C.; Stabile, Laura P. (Frontiers in Oncology, 2020)
Lung cancer mortality represents the leading cause of cancer related death in the United States and worldwide. Almost half of these deaths occur in female patients, making lung cancer the most common cause of cancer mortality in women with a higher annual mortality rate than breast, uterine, and ovarian cancers combined. Moreover, both lung cancer incidence and mortality rates among women are projected to significantly increase over the next decade. The distinct epidemiological, histological and biological presentation of non-small cell lung cancer (NSCLC) in women combined with extensive preclinical data have demonstrated that the female sex hormone β-estradiol (E2) plays an important role in NSCLC tumorigenesis, prognosis and treatment response. In this review, we summarize recent findings that support the existence of E2-driven pro-tumor effects on stromal and immune cells in the lung tumor microenvironment (TME), which may contribute to the pathogenesis of NSCLC. Estrogen receptors are expressed on stromal and immune cells, and estrogen-linked signaling pathways are known to be involved in regulating the response of both the innate and adaptive immune system. Immune evasion has been recognized as a “hallmark” of cancer and immunotherapy has re-defined standard of care treatment for NSCLC. Despite these advancements, the low response rates observed in patients treated with immune checkpoint inhibitors has led to a search for mediators of immunosuppression and ways to augment the action of these agents. We focus on emerging data describing sex differences that modulate immunotherapy efficacy in NSCLC, immunosuppressive properties of E2 that lead to a pro-tumor microenvironment, and the translational potential of altering the immune microenvironment by targeting the estrogen signaling pathway. E2-induced modulation affects multiple cell types within the TME, including cancer-associated fibroblasts, tumor infiltrating myeloid cells, and tumor infiltrating lymphocytes. All of these populations interplay with lung tumor cells via E2 and estrogen receptor engagement, ultimately shaping a pro-tumor microenvironment that may, in part, be responsible for the sex-based disparities observed in NSCLC. An improved understanding of the role of the estrogen pathway in NSCLC anti-cancer immunity may lead to novel therapeutic approaches for altering the TME to improve the efficacy of immunotherapy agents.